Active scour monitoring using ultrasonic time domain reflectometry of buried slender sensors. (14th December 2021) - Funderburk, Morgan L; Tran, Jamie; Todd, Michael D; Netchaev, Anton; Loh, Kenneth J
Abstract: Local scour is a growing cause of bridge failure in the United States and around the world. In the next century, the effects of climate changes will make more bridges susceptible to scour failure more than ever before. This study aims to harness the spatially continuous monitoring capabilities of ultrasonic time-domain reflectometry to detect a soil interface for the purposes of scour monitoring. In this study, a long, slender plate is coupled with two flexible piezoelectric devices that propagate Lamb waves along the length of the plate to form the scour sensor. The sensor was tested for sensitivity to external pressure using metal weights and was able to detect the position of the pressure up at a length of up to ∼20 feet. The sensor was tested under simulated scour conditions, being buried in sand at various depths. The results show that the Lamb wave scour sensor is capable of reliably detecting a soil interface at 1 ft intervals. The scour sensor was also able to detect uncompacted soil interfaces, which is important considering the issue of scour hole refill following an extreme event.